APB in-house training: MARA for MyRA / Muhammad Aiman Abdul Halim and Noor Azli Affendy Lee - Abdul Halim, Muhammad Aiman; Affendy Lee, Noor Azli (Academy of Language Studies, 2022)
On 1st April 2022, the department hosted the 'APB In-house Training: MARA for MyRA' webinar. The main objective of this event is to provide exposure to fellow APB lecturers regarding the Malaysia Research Assessment (MyRA) grant, especially since the grant application will be opened this year from the 4 April until 29 April. The invited speaker was Mr. Muhammad Azwan bin Azri, a lecturer from the Health Sciences Faculty of UiTMCPP who is also an active MyRA grant leader. Through this programme, APB lecturers were briefed about the requirements for the grant application, as well as some important tips and tricks for successful grant proposals. The 'APB In-house Training: MARA for MyRA' was first suggested by our Head of Department, Associate Professor Dr. Rofiza binti Aboo Bakar due to the need to meet the latest 2022 performance indicators (PI) for APB. Some of the performance indicators concerned are: PI061: Two principal investigators (PI) for national-funded research grants. PI064: Total amount of RM60,000 received from national-funded research grants.